Isolation and Identification of Fungi from Natural Fermentation of Guava Seeds - Darmasiwi, Sari; Pahlevi, Reza Dwi; Setiadi, Chris Elian Beryl (Jurnal Biologi Tropis, 2024)
Guava, a tropical fruit, is high in macro- and micronutrients. However, only 50% of the fruit’s parts are edible, while the peel and seeds are considered agro-industrial waste. Ruminants may benefit from the nutritional value of dehydrated guava seeds. Guava seeds processed by natural/spontaneous fermentation could boost amino acid content while also preventing antinutritional factors. However, more research is needed to determine the benefits and safety of using fermented guava seeds. The purpose of this study was to investigate fungi isolated from the natural/spontaneous fermentation of guava seeds. Guava seeds were fermented using sterile water and banana leaves, and incubated at 37 °C for 72 hours. Isolation was done on PDA medium for moulds and YMEA medium for yeast. The isolated fungi were characterized by their colony and cell morphology, as well as their physiological characteristics. Results showed that the yeasts from the genera Schizosaccharomyces, Pichia, and Cryptococcus were found to be primary microbes that play a role in the fermentation process, while the moulds from the Mucoraceae family are likely spoilage microbes that appear after the fermentation period.